Land Use Scenario Simulation for Erosion Control Using the Universal Soil Loss Equation (USLE) Method in Nagari Lawang, Agam Regency - Zawiyah Zawiyah; M. Agita Tjandra; Delvi Yanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Nagari Lawang is located in Agam Regency, West Sumatra, which is a nagari situated in the highlands with a slightly steep to very steep slope with the most types of land use in moors/fields. This can directly encourage erosion. This study aims to analyze the optimal land use pattern for reducing the rate of erosion in Nagari Lawang. The method used to calculate the erosion rate is the Universal Soil Loss Equation (USLE) and to obtain the optimal land use in reducing the erosion rate is a simulation with three scenarios. The results of the study showed that 47.29% of the Nagari Lawang land area was at an erosion rate above the tolerance erosion with the category of light to very heavy. Based on land use simulations, planning scenario III by allocating the use of shrubland into mixed gardens with planting according to contour lines and the use of shrub land into mixed forests is the best scenario because it can reduce erosion by 39.05% of the total erosion of Nagari Lawang. The reduction of erosion on the diverted land (moors/fields and shrubs) reached 45.83% of the existing condition, which was 2105.928 tons/ha/year. The best scenario land use can be used as a reference by policy makers and the community in determining appropriate land management actions in Nagari Lawang. Keywords: Erosion, Simulation, Land Use, USLE.